Paradygmat ideologicznego pojmowania społeczeństwa - Kozyr-Kowalski, Stanisław (Wydział Prawa i Administracji UAM, 1987)
The article presents those of the basic theses of Hegel's philosophy of society and history which most clearly reveal something that was called "ideology" by Marx and Engels. The paradigm of ideological interpretation of society created by Hegel still persists in scientific and non-scientific thought. Nowadays, it most often assumes the form of cryptotheory: a set of tacit assumptions which concern the construction, functioning and changes of global societies and are accepted in the analysis of particular theoretic and empirical problems. In the author's view, the basic elements of paradigm of ideological analysis of society are: 1) "objectivism" — i.e. considering the laws of social life and history to be the forces which are separate and independent of human actions, 2) monoideologism or ideological reductionism, 3) theoretical stateism, 4) identifying all economy with bourgeoios, early capitalist economy, 5) ideological determinism — i.e. assuming in the analysis of the impact of ideas on social life the same conception of macrositructural and macrohistorical causality which was the foundation of "vulgarly" materialistic determinisms: geographis, demographic, racial and antropological and economic.
The Paradigm of Ideological Formulation of Society